Ground gas handbook - Wilson, Steve (Whittles Pub. ; Distributed in North America by CRC Press, 2009)
Annotation This handbook provides practical guidance on assessing ground gas risk and the design of appropriate protection measures. It discusses the assessment of ground gas for Part II A sites and also includes information on the assessment of vapours. It provides information on gas generation and the analysis of gas flows in the ground, including the design of gas protection systems. It explains how to use the most recent assessment methods published by CIRICA, NHBC and BSI and highlights the differences between the various methods. It includes advice and recommendations about the validation and testing of protection systems as they are installed. Worked examples help explain the concepts and calculations.
Keywords: Landfill gases.; Waste gases -- Management.; Land use -- Planning.; Environmental engineering.; Land use, Urban.; Brownfields.; Sanitary landfills.; elektronické knihy; electronic books